ASSESSMENT OF ELEMENTS OF TOURIST INFRASTRUCTURE OF UKRAINE IN COMPARISON WITH SOME EU COUNTRIES - KOSHOVA, BOHDANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article considers the competitiveness of the elements of the tourist infrastructure of Ukraine in comparison with some countries of the European Union, which are the leaders in tourist revenues and flows in the analyzed region. An analysis of the dynamics of tourism development in neighbouring Poland, which in the 90’s was in similar to the domestic starting conditions. The study made it possible to clearly reflect the reasons for the low demand for the national tourism product. After all, the lag in the quality of hotel and restaurant services is not the main reason for low interest in the domestic tourism market. Morally and physically outdated material and technical base of social, informational, financial, transport and other types of infrastructure makes Ukraine less attractive in the eyes of domestic tourists. And the low level of knowledge of foreign languages, non-compliance with legal norms and rules at the national level makes grazing the country in general unattractive for the demanding foreign tourist. The modern tourist, being able to choose the directions and quality of rest in today’s conditions, will not want to travel to a region with many unknowns, where they will not guarantee him peace, comfort and safety. That is why it is so important to analyze the level of development of some elements of tourism infrastructure in developed EU countries (Germany and the Netherlands) to indicate the consequences of its radical restructuring to ensure economic growth at the national level, where neighbouring Poland was chosen. With its rich natural and recreational resources, Ukraine can rightfully become a world leader in green, rural, health, active, cognitive tourism, and the diversity of landscapes combined with the temperate climate makes its landscapes especially attractive to tourists from highly urbanized areas. more and more.